Environmental dynamics and land cover change in Kotri, Pakistan: A 35-year NDVI assessment - Awais, Muhammad; Bux, Hadi; Arroba; Aasma; Zehra, Ghulam; Mumtaz, Sonia (Journal of Himalayan Earth Sciences, 2026)
Land cover change is critical in semi-arid landscapes, and has significant implications for ecosystem services, agricultural management and water-resource planning. Local scale assessments are limited, but Kotri Taluka in the lower Indus Basin, Pakistan is ecologically and agriculturally important and has a long history of need for long term assessment at that scale. The land cover change was quantified in the Kotri Taluka from 1990 to 2025 using multi-date NDVI classification in Landsat. Five images were acquired during the monsoon season: one Landsat 4-5 TM in 1990, and four Landsat 8-9 OLI in 2013, 2020, 2022 and 2025, were classified as water, non-vegetated land, sparse vegetation, agriculture and dense vegetation. The area change of each class was computed and two-proportion z-tests were used to compare proportional changes between 1990 and 2025. Non-vegetated land decreased from 89,740 ha (61.12%) in 1990 to 65,002 ha (44.30%) in 2025, a 27.6% relative decrease (p < 0.001). Agriculture increased from 4,965 ha (3.38%) to 15,292 ha (10.40%), a 208% relative increase (p < 0.001). Total vegetation increased from 35.72% to 53.43%, a net gain of 25,960 ha (p < 0.001). Sparse vegetation increased by 13,587 ha (+30.4%, p < 0.001), while dense vegetation increased by 2,046 ha (+72.2%, p < 0.01). The analysis by period revealed non-linear dynamics: growth between 1990-2013, a decline between 2013-2020 and a rise again between 2020-2025. The results are baseline data for land use planning, agricultural sustainability and water resource management in Lower Indus Basin.